2018
DOI: 10.3389/fimmu.2018.01856
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Asthma Favors Brucella Growth in the Lungs of Infected Mice

Abstract: Allergic asthma is a chronic Th2 inflammatory disease of the lower airways affecting a growing number of people worldwide. The impact of infections and microbiota composition on allergic asthma has been investigated frequently. Until now, however, there have been few attempts to investigate the impact of asthma on the control of infectious microorganisms and the underlying mechanisms. In this work, we characterize the consequences of allergic asthma on intranasal (i.n.) infection by Brucella bacteria in mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“…In addition, intestinal eosinophils have an increased half-life over blood or lung eosinophils (106). Specific eosinophil subsets are continually being identified (143), including a GR1 ϩ eosinophil population (144) (GR1 is typically a neutrophil marker). This makes eosinophil identification all the more difficult and highlights the importance of using tools such as the eosinophil reporter mouse (145) to assess eosinophil subsets and functions.…”
Section: Reinterpreting Results and Use Of New Technologiesmentioning
confidence: 99%
“…In addition, intestinal eosinophils have an increased half-life over blood or lung eosinophils (106). Specific eosinophil subsets are continually being identified (143), including a GR1 ϩ eosinophil population (144) (GR1 is typically a neutrophil marker). This makes eosinophil identification all the more difficult and highlights the importance of using tools such as the eosinophil reporter mouse (145) to assess eosinophil subsets and functions.…”
Section: Reinterpreting Results and Use Of New Technologiesmentioning
confidence: 99%
“…Similar to our results, infection with intracellular pathogens of the Brucella family is reportedly exacerbated by exposure to allergens via IL-4/STAT6 signaling. However, infection with Streptococcus pneumoniae , an extracellular pathogen, is alleviated by allergen exposure, whereas Mtb infection is not altered under conditions of comorbidity [ 26 ]. Monin et al studied the effect of Aspergillus fumigatus , which commonly coinfects NTM, on Mycobacterium abscessus infection.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of NTM-PI and allergic asthma is likely to accelerate the progression of both diseases; thus, a general understanding of comorbid conditions regarding pathology and immunology is clinically important. Although many studies have revealed mycobacterial infection-related conditions comorbid with allergic asthma from various perspectives of allergic asthma [ 23 , 24 ], only a few studies have investigated immunological progression [ 25 , 26 ]. Moreover, to our knowledge, whether these chronic diseases influence one another has not been investigated in previous experimental studies or clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…infected wild-type mice. Brucella -infected neutrophils have been described in pathological conditions (69). To our knowledge, this is the first description of Brucella -infected fibroblasts in vivo in wild-type mice.…”
Section: Discussionmentioning
confidence: 99%